De jiao : a religious movement in contemporary China and overseas : purple qi from the East. - Formoso, Bernard (NUS Press, 2010)
De Jiao ("Teaching of Virtue") is a China-born religious movement, based on spirit-writing and rooted in the tradition of the "halls for good deeds," which emerged in Chaozhou during the Sino-Japanese war. The book relates the fascinating process of its spread throughout Southeast Asia in the 1950s, and, more recently, from Thailand and Malaysia to post-Maoist China and the global world.